CEH : Certified Ethical Hacker Practice Exams - Walker, Matthew (McGraw-Hill Education, 2022)
Don't Let the Real Test Be Your First Test! Fully updated for the CEH v11 exam objectives, this practical guide contains more than 550 realistic practice exam questions to prepare you for the EC-Council's Certified Ethical Hacker exam. To aid in your understanding of the material, in-depth explanations of both the correct and incorrect answers are provided for every question. Designed to help you pass the exam, this is the perfect companion to CEH"!Certified Ethical Hacker All-in-One Exam Guide, Fifth Edition. Covers all exam topics, including: Ethical hacking fundamentals Reconnaissance and footprinting Scanning and enumeration Sniffing and evasion Attacking a system Hacking web servers and applications Wireless network hacking Mobile, IoT, and OT Security in cloud computing Trojans and other attacks, including malware analysis Cryptography Social engineering and physical security Penetration testing Online test engine provides full-length practice exams and customizable quizzes by chapter or exam domain